Antioxidant and Emulsifying Activities of Corn Gluten Meal Hydrolysates in Oil‐in‐Water Emulsions. (16th October 2019) - Shen, Yanting; Hu, Ruijia; Li, Yonghui
Abstract: Corn gluten meal (CGM) is a protein‐rich coproduct generated during corn wet milling. In this study, CGM was hydrolyzed using Neutrase protease for 1 and 3 hours, respectively, to obtain antioxidative corn gluten meal protein hydrolysates (CGMPH), which could be a potential antioxidant in various products to retard lipid oxidation. Our objective was to evaluate the emulsion properties and oxidation stability of oil‐in‐water emulsions containing different types (1‐hour and 3‐hour hydrolysates) and amounts of CGMPH. The results showed that the emulsions with CGMPH had significantly improved oxidative stability than the control based on both peroxide value and thiobarbituric acid reactive substance (TBARS) analysis. The emulsion with higher concentration of CGMPH (e.g., 5 mg mL −1 ) showed more effective inhibition on lipid oxidation. The emulsion turbidity of 1‐hour CGMPH at 2.5 mg mL −1 had a lower value than that of other emulsions, and overall, the turbidity for 3‐hour CGMPH had a slightly higher value than that with 1‐hour CGMPH. Addition of CGMPM did not affect emulsion morphology and droplet sizes. Zeta potential analysis showed that emulsions with 1‐hour hydrolysate had more negative charges with better emulsion stability than that with 3‐hour hydrolysate at the same pH. In conclusion, the CGMPH were able to inhibit lipid oxidation in reducing the formation of hydroperoxides and TBARS, and could be a potential functional antioxidant for food emulsion applications.